2011
DOI: 10.1002/ijc.25754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an aggressive prostate cancer predisposing variant at 11q13

Abstract: Prostate cancer is the most frequently diagnosed cancer in men; however, the genetic basis of susceptibility remains elusive. The EMSY gene is located in the prostate cancer linked chromosome region at 11q13.5. The aim of this study was to screen EMSY for sequence variants and to evaluate its association with the risk of prostate cancer. We performed a Finnish population-based case-control study with 923 controls, 184 familial prostate cancer cases and 2,301 unselected prostate cancer cases. Variants were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…Interestingly, the aggressive SNP was segregated with breast cancer in a prostate cancer family [28]. However, in the present study, we did not detect the aggressive SNP.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Interestingly, the aggressive SNP was segregated with breast cancer in a prostate cancer family [28]. However, in the present study, we did not detect the aggressive SNP.…”
Section: Discussioncontrasting
confidence: 81%
“…We previously examined the association of EMSY SNPs with prostate cancer predisposition and identified a rare intronic SNP that increases the risk of aggressive prostate cancer (referred to as aggressive SNP) [28]. Interestingly, the aggressive SNP was segregated with breast cancer in a prostate cancer family [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggested the BRCA2-independent function of EMSY. Besides, recent studies have shown that amplification of EMSY was also associated with other cancers such as prostate and pancreatic cancers [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…EMSY localizes to the sites of DNA repair following DNA damage and maps to chromosome 11q13.5, 100 kb centromeric to the GARP gene, a locus that is known to be involved in a number of cancers including breast, ovarian and prostate cancers (Nurminen et al, 2011). Recently Nurminen et al showed that 11q13.5 contributes to prostate cancer predisposition with complex genetic structure and is associated with prostate cancer death (Nurminen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%